Implications of product upgrading confronting supplier remanufacturing. Issue 19 (1st October 2020) - Qian, Zhifeng; Chai, Junwu; Li, Hengyu; Yan, Wei; Chen, Hong
Abstract : It is generally believed that new products upgrading is an effective strategy to deal with the cannibalisation problem from remanufacturing, however, it is not clear how the new product upgrading strategy affect the decision-making of the downstream manufacturer and the upstream supplier. By examining the relationship between supplier remanufacturing profits and product cannibalisation, we develop two models to investigate the implications of the manufacturer's product upgrading confronting supplier remanufacturing. The results show that an product upgrading strategy can effectively enhance the manufacturer's profits if the investment cost is relatively low. Although the product upgrading strategy may hinder the remanufacturing operations, it will always be beneficial for the wholesaling of the supplier's new products. Therefore, the upgrading strategy can mitigate cannibalisation problems and create an optimal pareto improvement for both parties. Finally, we conduct a data analysis to provide additional managerial insights regarding the supply chain.